Development of Web-Based E-Module Learning with SSI Approach on Hormone Material in Human Reproduction to Improve Critical Thinking Skills and Self-Awareness of High School Students Phase F - Putri Nuri Nirwana; Bernadetta Octavia (Jurnal Penelitian Pendidikan IPA, 2025)
This development research uses the ADDIE model. The development design consists of five stages, namely, Analysis, Design, Development, Implementation, and Evaluation. The learning approach used in this e-module is the SSI (Socio-scientific Issue) approach. The learning web-based e-module with the SSI approach was evaluated by material experts, media experts, practitioners and tested its effectiveness on students of class XI IPA SMA N 1 Jebus using a quasi experiment with a random control group pretest-postest design. Data collection techniques used in this study were observation, interview, questionnaire, test, and documentation. The data from this study were analyzed by descriptive and inferential stastics with the MANOVA test. The results showed that: 1) web-based e-module learning with the SSI approach is feasible to use in learning biology based on the assessment of material experts and media experts; 2) web-based e-module learning with the SSI approach is practical to use in learning biology based on the assessment of biology teachers and students; 3) web-based e-module with the SSI approach effectively improves students' critical thinking skills and self-awareness, as evidenced by the results of the MANOVA test which shows significant differences (Sig value 0.000 <0.05) between students who use and do not use the e-module.